Effect of Surfactant Concentration on the Characteristics of Polyaniline Nanocomposite - Tayebi, H.; Rastar, Amir; Hoseinpour, Alireza (Asian Journal of Chemistry, 2011)
Polyaniline nanocomposite was prepared by chemical oxidative polymerization of aniline using [(NH4)2S2O8] as an oxidant in the presence of sodium dodecylbenzenesulfonate (DBSNa) as surfactant. The product was characterized in terms of morphology with scanning electron microscopy and chemical structure by fourier transform infrared spectroscopy.